2017
DOI: 10.1002/2016gl071743
|View full text |Cite
|
Sign up to set email alerts
|

The effects of teleconnections on carbon fluxes of global terrestrial ecosystems

Abstract: Large‐scale atmospheric circulation patterns (i.e., teleconnections) influence global climate variability patterns and can be studied to provide a simple framework for relating the complex response of ecosystems to climate. This study analyzes the effects of 15 major teleconnections on terrestrial ecosystem carbon fluxes during 1951–2012 using an ensemble of nine dynamic global vegetation models. We map the global pattern of the dominant teleconnections and find that these teleconnections significantly affect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
64
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 81 publications
3
64
0
Order By: Relevance
“…The multidecadal behaviors of ET a and carbon fluxes over the CONUS to PDO and AMO were not clearly found in prior studies (e.g., Martens et al, ; Miralles et al, ; Zhu et al, ) due in part to the relatively short lengths of ET a data and remote sensing products. Despite uncertainty associated with the R n estimates, the first PC of SEDI240 was almost a mirror image of the smoothed AMO over the last 60 years, emphasizing the modulation of the Atlantic Ocean.…”
Section: Discussionmentioning
confidence: 76%
“…The multidecadal behaviors of ET a and carbon fluxes over the CONUS to PDO and AMO were not clearly found in prior studies (e.g., Martens et al, ; Miralles et al, ; Zhu et al, ) due in part to the relatively short lengths of ET a data and remote sensing products. Despite uncertainty associated with the R n estimates, the first PC of SEDI240 was almost a mirror image of the smoothed AMO over the last 60 years, emphasizing the modulation of the Atlantic Ocean.…”
Section: Discussionmentioning
confidence: 76%
“…Regarding the possible causes of RN reductions, previous studies have suggested that cloud coverage and air pollution and aerosol loading from rapid urbanization are potential reasons (Qian, Kaiser, Leung, & Xu, 2006;Xia, Wang, Chen, & Liang, 2006;Yang et al, 2009). Zhu et al (2017) found that large-scale atmospheric or coupled atmosphere-ocean modes are strongly associated with cloud cover across the world, which leads to RN variations. Moreover, with a weaken WND in China, air pollution and aerosol loading cannot be rapidly dispersed, which results in the further decrease in RN (Yang et al, 2009).…”
Section: Causes For Trends In Meteorological Factorsmentioning
confidence: 99%
“…Furthermore, by considering the importance of ET 0 for the estimation of crop water demand and drought forecasting systems (McEvoy et al, 2016), obtaining detailed information about ET 0 is critical before developing countermeasures for policy makers. Large-scale atmospheric or coupled atmosphere-ocean modes of climate variability (usually referred to as teleconnections due to their long-distance range of influence) can provide a useful framework for linking ET 0 to climate fluctuations via influencing climate variables (e.g., wind speed, solar radiation, temperature, and relative humidity; Chen, Li, & Pryor, 2013;Li & Chen, 2014;Yu, Zhong, Bian, & Heilman, 2015;Zhu et al, 2017). Given more knowledge of atmospheric system processes and the improved capability of future teleconnection predictions (Alexander, Matrosova, Penland, Scott, & Chang, 2008;Derome, Lin, & Brunet, 2005;Yang et al, 2015;Zheng, Fang, Zhu, Yu, & Li, 2016), estimating future ET 0 has become more possible using historical and predicted teleconnection patterns.…”
mentioning
confidence: 99%
“…In any case, those concerned with temperature recognise 1) that around half the solar energy that falls on land is converted into the evaporation of water thus cooling the land surface (Pokorny et al 2010;Wang and Dickinson 2012), 2) that water vapour is the dominant greenhouse gas on our planet (Ravishankara 2012;Sherwood et al 2010) and 3) that the distribution of clouds and snow cover exert a major influence on planetary albedo (the proportion of incident light reflected back into space) and energy balance (Donohoe and Battisti 2011;. Those concerned with carbon recognise that water is the most limiting factor for terrestrial ecosystem carbon uptake, and that uncertainties over water imply uncertainties over biomass and carbon fixation (Polis 1999;Good et al 2013;Bernacchi and VanLoocke 2015;Thorley et al 2015;Viglizzo et al 2016;Taylor et al 2017;Zhu et al 2017). Furthermore, those concerned with environmental conservation, stability and the maintenance of species diversity recognise both the significance of freshwater biodiversity (supporting over 126,000 species of plants and animals, many of them vulnerable, on 0.8% of the world's surface, Garcia-Moreno et al 2014) and the links between terrestrial diversity and moisture (Kreft and Jetz 2007;Sheil et al 2016;Viglizzo et al 2015).…”
Section: Introductionmentioning
confidence: 99%